1975
DOI: 10.1001/archpedi.1975.02120450035007
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal Gynecomastia and Transient Elevation of Serum Estradiol Level

Abstract: \s=b\ Serum levels of testosterone, estradiol, progesterone, 17\g=a\-hydroxyprogesterone, follicle-stimulating hormone, and luteinizing hormone were measured in 16 boys with pubertal gynecomastia. Six patients had elevated serum estradiol concentrations, and four of these six also had elevated progesterone levels. Serum estradiol/testosterone ratios were high for the stage of puberty in 11 of the 16 patients. In five patients who had two or more determinations, the steroid concentrations returned toward or int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…13,14 Another reported slightly higher mean estradiol levels in adolescent males with gynecomastia as compared with those without. 15 It has been speculated that this relative estrogen excess is a result of increased peripheral conversion (via aromatase) of adrenal androgens 16 and gonadal testosterone 15,17,18 to estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Another reported slightly higher mean estradiol levels in adolescent males with gynecomastia as compared with those without. 15 It has been speculated that this relative estrogen excess is a result of increased peripheral conversion (via aromatase) of adrenal androgens 16 and gonadal testosterone 15,17,18 to estradiol.…”
Section: Discussionmentioning
confidence: 99%
“…Elevations in estrogen concentrations may occur through increased peripheral conversion of adrenal androgens and gonadal testosterone to estradiol via the enzyme aromatase [3]. However, previous studies [7,9,10] have found conflicting results when comparing the hormonal profiles between adolescents with and without gynecomastia. No difference in sex hormone profiles, decreased free testosterone levels, and slightly higher estradiol concentrations have all been reported in adolescents with gynecomastia compared with nonaffected boys.…”
Section: Pathogenesis Of Pubertal Gynecomastiamentioning
confidence: 99%
“…Breast ultrasonography (USG), scrotal USG and abdominal computerized tomography (CT) of the abdomen can also be used as well as magnetic resonance imaging of the pituitary. A percutaneous biopsy should be taken, at times, when it is difficult to differentiate gynecomastia and breast cancer [5,6,[32][33][34][35][36].…”
Section: Diagnostic Testingmentioning
confidence: 99%